The Effect of Augmented Reality in Online Beauty Retail on Brand Perception - Mulyana Sari; Khaerunnisa Nur Fatimah Syahnur (Hasanuddin Economics and Business Review, 2026)
One notable innovation is the use of Augmented Reality (AR), which allows consumers to virtually try on products, enhancing the online shopping experience. This study aims to examine the impact of AR usage and consumer engagement on the brand perception of Maybelline products on the Shopee e-commerce platform. Employing a quantitative explanatory research method, data were obtained through an online survey of 200 Shopee users in Indonesia who had interacted with AR features when exploring Maybelline products. The research investigates the relationships between AR, consumer engagement, and brand perception in the context of digital beauty marketing. The findings reveal that both AR usage and consumer engagement have a significant positive effect on brand perception. Moreover, consumer engagement is found to partially mediate the relationship between AR and brand perception. These results highlight the strategic importance of immersive technologies and active consumer involvement in building strong brand impressions. The study contributes to the growing body of knowledge on digital marketing in the beauty industry and offers practical insights for brands aiming to leverage AR tools to enhance customer experience and strengthen brand positioning in competitive e-commerce environments.